THE USE OF READER’S THEATER IN TEACHING READING - Peni; Dewi Sartika (Language and Education Journal, 2019)
One of the ways to get new information is by reading. By reading, students are expected to get knowledge and be familiar with what is stated in the content of the text. Nevertheless, students are still have some problems in comprehending the reading text which makes their reading achievement were low. To overcome the students’ problems in reading, the teacher could implement the reader’s theater strategy. Therefore, this study was to investigate the effectiveness of the reader’s theater on students’ reading comprehension achievement. To conduct the research pretest posttest nonrandomized control group design, involving two groups was applied. The samples of this research were the students of the eleventh-grade students of SMA Negeri 2 Tanjung Raja. Based on the calculation using independent sample t-test, it was indicated that the reader’s theater could improve students’ reading comprehension achievement. The use reader’s theater was likely to be more effective in improving students’ reading achievement particularly in terms of vocabulary and comprehending the text. In addition, readers’ theater strategy can help the teacher in teaching reading narrative text because by using readers’ theater, students focused on the content of the text